EXPLORING URBAN VOIDS: STUDYING URBAN REGENERATION - Chhavi Dhingra; Shashi Saxena; Ankita Srivastava (International Journal of Urban Design and Development, 2023)
The rapid urbanization of a city is beneficial for its economic and cultural growth, but it stems from a growing concern over the effects of urbanization on the environment, human health, and well-being. This rapid urbanization results in the development in the formation of voids in the urban fabric. These voids create the possibility of places in the city that are overlooked and underutilized during the development of the city. This study can help provide valuable insights into how rapid and innovative infrastructural growth can harm the inhabitants of the city. Starting a dialogue can help create more environmentally and human-friendly infrastructure in cities; helping improve the quality of life in urban areas.
Keywords: Urban voids; overhead structures; urban development; urban regeneration